The Effect Of Perceived Organizational Support, Organizational Justice On Employee Performance With Job Satisfaction As A Mediation Variable At PT Sampoerna Kayoe Bukateja - Muhammad Ihza Alfania; Alfato Yusnar Kharismasyah; Fatmah Bagis; Luthfi Zamakhsyari (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to examine the effect of Perceived Organizational Support, organizational justice on employee performance with job satisfaction as a mediating variable. The population in this study were employees of PT. Sampoerna Kayoe Bukateja engaged in the production of processed wood in Purbalingga. This study applies a quantitative approach method. The sample used was 185 employees and respondents were obtained using non-probability sampling with purposive sampling. The type of data in this study is primary data and the instrument used in data collection is a questionnaire with a 5-point Likert scale measurement. While the analysis technique used is SEMPLS version 3.0. The results of the study indicate that Perceived Organizational Support and organizational justice have a positive and significant effect on job satisfaction, Perceived Organizational Support and organizational justice have a positive and significant effect on employee performance, Perceived Organizational Support and organizational justice have a positive and significant effect on satisfaction, satisfaction mediates the effect of organizational justice on employee performance, and satisfaction mediates the effect of Perceived Organizational Support on employee performance.